Performance of Papanicolaou Testing and Detection of Cervical Carcinoma In Situ in Participants of Organized Cervical Cancer Screening in South Korea - Han, Mi Ah; Choi, Kui Son; Lee, Hoo-Yeon; Jun, Jae Kwan; Jung, Kyu Won; Kang, Sokbom; Park, Eun-Cheol (PLOS ONE, 2012)
Background The present study measured the performance of the Papanicolaou (Pap) test and detection of cervical carcinoma in situ (CIS) and cancer in participants of organized cervical cancer screening in South Korea, and examined differences in the proportion of CIS according to socio-demographic factors. Methods Data were obtained from the National Cancer Screening Program and National Health Insurance Cancer Screening Program databases. We analyzed data from 4,072,997 screenings of women aged 30 years or older who underwent cervical cancer screening by Pap test between January 1, 2005 and December 31, 2006. We calculated the performances of the Pap test and compared that according to socio-demographic factors. Results The positivity rate for all screenings was 6.6%. The cancer detection rate (CDR) and interval cancer rate (ICR) were 0.32 per 1,000 screenings, and 0.13 per 1,000 negative screenings, respectively. About 63.4% of screen-detected CIS+ cases (CIS or invasive cervical cancer) were CIS. The CDR and ICR, and percentage of CIS among all CIS+ were significantly different by age group and health insurance status. The odds ratios of CDR and ICR were higher for Medical Aid Program (MAP) recipients compared with National Health Insurance (NHI) beneficiaries. The likelihood of a detected CIS+ case to be CIS was significantly lower among MAP recipients than among NHI beneficiaries. Conclusions The difference in performance of cervical cancer screening among different socio-demographic groups may indicate an important influence of socio-demographic factors on preventive behavior. The findings of the study support the critical need for increasing efforts to raise awareness and provide more screening in at-risk populations, specifically low-income groups.